Qualitative analyses on the classification model of bystander behavior in cyberbullying - Rong, Kexin; Chu, Xiaowei; Zhao, Yujing (Frontiers in Psychology, 2023)
Introduction Bystanders account for the largest proportion of those involve in cyberbullying and play an important role in the development of cyberbullying incidents. Regarding the classification of bystander behavior in cyberbullying, there exist some limitations in the previous research, such as not considering the complexity of the online environment. Therefore, this study constructed a new classification model of bystander behavior in cyberbullying. Methods By separately utilizing questionnaires and experimental methods, the study collected participants’ behavioral intentions and actual behavioral responses to deal with cyberbullying incidents. Results Based on two qualitative studies, this study summarized a new classification model, which included three first-level factors and six second-level factors. Specifically, the classification model included positive bystander behavior (i.e., pointing at the victim, bully, and others), neutral bystander behavior (i.e., inaction), and negative bystander behavior (i.e., supporting and excessively confronting the bully). Discussion The classification model has important contributions to the research on bystander behavior in cyberbullying. This model helps researchers to develop more effective intervention approaches on cyberbullying from the perspective of each category of bystander behavior.